2021
DOI: 10.4236/ojo.2021.115017
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Periarticular Ganglia (Synovial Cysts) of the Hip with Compression of the Obturator Nerve, Concomitant with Lesions of the Ligamentum Teres—A Report of 3 Cases

Abstract: Background: Synovial cysts of the hip are commonly found in patients with intra-or extraarticular pathologies of the joint. Symptoms are mostly unspecific. To date there are no guidelines for a gold standard of treatment. Aim of this article is to show up how lesions of the ligamentum teres (LT) might possibly lead to a specific formation of synovial cysts of the hip joint and how this can be treated arthroscopically. Methods: This case series included 3 patients with ganglia of the hip. All patients had impin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…There is the potential for this to communicate with the joint capsule and become distended in the presence of a hip joint effusion or synovial proliferation [16] . Moreover, several case reports have described ganglion or synovial cysts arising from this location resulting in obturator nerve entrapment [ [17] , [18] , [19] 20 ]. The lesion in our patient was fully excised with clear pathological margins without breaching the hip joint capsule which confirmed that this lesion was external to the capsule and not intra-articular.…”
Section: Discussionmentioning
confidence: 99%
“…There is the potential for this to communicate with the joint capsule and become distended in the presence of a hip joint effusion or synovial proliferation [16] . Moreover, several case reports have described ganglion or synovial cysts arising from this location resulting in obturator nerve entrapment [ [17] , [18] , [19] 20 ]. The lesion in our patient was fully excised with clear pathological margins without breaching the hip joint capsule which confirmed that this lesion was external to the capsule and not intra-articular.…”
Section: Discussionmentioning
confidence: 99%